Ultrasound characteristics of abdominal vascular compression syndromes - Liu, Yan; Zheng, Haining; Wang, Xiaoqing; Wang, Zi; Zhu, Qiang; Wen, Chaoyang; Tong, Yisha (Frontiers in Cardiovascular Medicine, 2023)
Abdominal vascular compression syndromes (AVCS) are caused by either compression of abdominal blood vessels by adjacent structures or compression of abdominal organs by neighboring blood vessels. Such compressions can result in a variety of clinical symptoms. They are not commonly seen in ultrasound practices, and may have been underrecognized and underdiagnosed. This article reviews clinical features, and ultrasound characteristics and diagnostic criteria of four AVCS, namely, celiac artery compression syndrome, renal vein compression syndrome, iliac vein compression syndrome, and superior mesenteric artery syndrome to increase awareness of these conditions to ultrasound practitioners. Most ultrasound criteria for AVCS are based on studies using small sample size and caution should be taken if these criteria are used.